BIODEGRADABILITY OF IRRADIATED POLY(BUTYLENE SUCCINATE-co-ADIPATE) IN THE PRESENCE OF ADITIF - Meri Suhartini (Jurnal Sains Materi Indonesia, 2006)
BIODEGRADABILITY OF IRRADIATED POLY(BUTYLENE SUCCINATE-co-ADIPATE) IN THE PRESENCE OF ADITIF. Poly(butylene succinate-co-adipate) (PBSA) was mixed with Silicon dioxide, Carbon black, and Trimethallyl Isocyanurate (TMAIC), respectively. The rate of biodegradability was investigated using Microbial Oxidative Degradation Analyzer (MODA), enzymatic and soil burial test. It was pointed out that the rate of biodegradability of irradiated PBS1 containing 2% silicon dioxide and 2% carbon black, respectively, much faster than that of irradiated pure PBS1. This phenomenon is due to the enlargement of the sample’s surface caused by the presence of inorganic material in the sample, thus easier for enzymes to introduce inside polymer. On the other side irradiated PBSA contains TMAIC has lower biodegradation rate than irradiated original PBSA at the same irradiation dose, in this case the biodegradation rate depend on gel fraction of the sample.